2016
DOI: 10.1016/j.jmatprotec.2016.03.009
|View full text |Cite
|
Sign up to set email alerts
|

A new value for Johnson Cook damage limit criterion in machining with large negative rake angle as basis for understanding of grinding

Abstract: Grinding is one of the most complex manufacturing processes in industry and understanding its physics is still fairly limited due to the stochastic nature of the process. The physics behind the grinding process can be better understood through thermomechanical analysis of grain-material interactions, enabling the optimization of the process and grinding tool. When simulating the chip formation in machining processes, difficulties arise when the negative rake angle is large, when thermal effects on the tool and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(8 citation statements)
references
References 41 publications
0
7
0
1
Order By: Relevance
“…With d1, d2, d3 and d4, parameters of Johnson Cook's law at fracture associated with the machined material, σ m is the hydrostatic pressure, and is the equivalent von Mises stress [21][22][23][24][25]. Damage…”
Section: Thermo-viscoplastic Models Of Johnson-cook and Of Damagementioning
confidence: 99%
“…With d1, d2, d3 and d4, parameters of Johnson Cook's law at fracture associated with the machined material, σ m is the hydrostatic pressure, and is the equivalent von Mises stress [21][22][23][24][25]. Damage…”
Section: Thermo-viscoplastic Models Of Johnson-cook and Of Damagementioning
confidence: 99%
“…Given this, once the cutting edge becomes even slightly worn, the cutting chips become lodged on and adhere to the flank face. Thus, the insufficient flank clearance leads to the large negative rake angle at the local point of view of the tip of the cutting edge (Akbari , et al 2016). The insufficient flank clearance at the foot of the cutting edges renders the cutting process inefficient.…”
Section: Developed Pcd Blade Cutting Edge Formation and Process Evalumentioning
confidence: 99%
“…To investigate the chip removal mechanism of the PCD ball end mill, an orthogonal cutting with a single-point PCD tool is studied. The concept is a helps-better understand of the chip formation mechanism and other phenomena in varieties of both traditional cutting and the action of abrasive grits (Akbari et al, 2016;Baizeau et al, 2015;Ding et al, 2020). Previous studies reported that chip can be generated on ductile materials by using cutting tool having a large negative rake down to −75° (Fang, 2005, Komanduri, 1971.…”
Section: Introductionmentioning
confidence: 99%